Screening and evaluation of potential microbial bio-activators used in sewage sludge composting - Makpal Bostubayeva; Elmira Baimbetova; Meruyert Makenova; Nazymgul Shumenova; Roza Sarmanova; Ainash Nauanova (Caspian Journal of Environmental Sciences)
Forty pure microbial cultures have been isolated from sewage sludge to develop biopreparations using the microbiological screening method. Among all studied microorganisms sixteen strains of different taxonomic groups (2 strains of each Bacillus and Streptomyces, 7 strains of Pseudomonas, and 1 strain of each of the following Acinetobacter, Rhizobium, Pseudarthrobacter, Sphingomonas, and Rothia) were selected providing the best cellulose-degrading ability, as well as having good growth and quick biomass accumulation on various substrates. The isolates were additionally tested for the ability to consume organic and mineral nitrogen species, and to encourage seedlings’ growth. Moreover, we have evaluated the nitrogenase activity for some strains. As a result, the following strains of Bacillus megaterium № 10, Rhizobium pusense № 25, Sphingomonas paucimobilis № 49, Pseudomonas fluorescens № 83, Streptomyces albidoflavus № 81, Streptomyces graminearus № 61 demonstrated the potential to be used as bio-activator for sewage sludge composting and as multifunctional biologics in crop production.